Multi-omics analysis profile oral tumor module clusters to reveal the potential pathogenic mechanism - Liu, Jun; Zhao, Chaoyue; Yang, Song; Dong, Chen (Cellular and Molecular Biology, 2020)
Oral tumors are malignant cancers caused by abnormal proliferation or pathological changes of soft or hard tissues in the oral cavity. Serious cases may pose a threat to life. However, its precancerous lesions remain unclear. This study is based on a comprehensive strategy to explore a multi-factor-driven oral cancer barrier module, which is an attempt to describe the pathogenesis of the disease and potential regulatory drugs from a global perspective. Functional disease modules were identified by constructing a protein-specific interaction network in patients' oral tissues. Then, comprehensive pathogenesis was explored through combination with analysis of functional and signaling pathway enrichment, prediction of key regulatory factors. It was found that these specifically expressed proteins and their interactions often play a pivotal part in oral tumors. This is reflected in the results of functional and pathway enrichment of modulating genes, which show that they are mainly involved in various immune responses, inflammatory reactions, oral plaque, and oral ulcer-related regulatory processes. This may represent the potential pathogenesis of oral tumors. On the predictive analysis of regulators, a series of ncRNAs (including miR-590, CRNDE and miR-340) and transcription factors (including E2F1, MYC and TP53) were identified that have potential important regulatory effects on oral tumors. These key regulators may manipulate a crucial part of the module sub-network and then work together to mediate the occurrence of oral tumors. On the comprehensive Multi-omics module analysis, the specific proteins and their interactions in patients' oral tissues were identified, while the prominent pivotal regulators were involved in the different pathogenic functions of oral tumors.